Long-term Patient-reported Functional Outcome after Pelvic Ring Injuries: Analysis using Two Different Types of Outcome Scores - Sameer Aggarwal; Lav Mehta; Sandeep Patel; Vishal Kumar; Prasoon Kumar (Journal of Orthopaedic Case Reports)
Introduction: Pelvic ring injuries lead to significant patient morbidity and mortality. We evaluated long-term (>1 year) functional outcome of these patients using patient-reported outcome measures) using both generic health-specific and disease-specific outcome instruments. Materials and Methods: Pelvic ring injury patients seen between 2015 and 2020 were called for a follow-up visit. Patient’s demographic profile, mode and pattern of injury, associated injuries, management, and complications were recorded. Functional outcome assessment was made using two generic health-specific scores (SF-36 and short musculoskeletal functional assessment [SMFA]) and three disease-specific scores (Majeed pelvic score [MPS], Iowa pelvic score [IPS], and pelvic discomfort index [PDI]). Statistical analysis was performed to find the correlation between the two types of scoring systems. SF-36 scores of the study population were compared with normative data from the general population. Results: Of 56 patients (37 males, 19 females, mean age 32 years), there were 40 Tile B type and 16 Tile C type. 27 patients had other orthopaedic injuries, while 24 had nonorthopaedic injuries (14 – urological). 42 patients were operated and 14 were conservatively managed. The mean follow-up duration was 26.8 months. Mean (standard deviation [SD]) SF-36 physical component summary score was 64.01 (22.89) and mental component summary score was 63.79 (23.31). SMFA dysfunction index and SMFA bother index mean (SD) were 22.41 ± 11.75 and 25.97 ± 14.12, respectively. Mean (SD) MPS came as 85.93 (12.89) with 37 patients graded as “excellent.” The mean (SD) of IPS and PDI scores were 78.61 (9.40) and 21.70 (16.59), respectively. There was no statistical difference between the two types of scores when assessed using Spearman correlation tests. However, on comparison of study population mean SF-36 subset scores with general population norms, no domain of SF-36 could reach norm values. MPS cutoff of >85 (“excellent” outcome) could not include in itself a sufficient percentage of population with at-par SF-36 scores. Long-term sequelae of trauma were significantly associated with poor quality of life scores. Conclusion: Long-term physical functioning and quality of life in patients with pelvic ring injuries seem to be fair, although they are significantly lower than that of their peers in the general population.